Use of the Multistakeholder Dialogue Platform approach for effective participation of local communities in interventions for biodiversity conservation and enhanced livelihoods across the Kenya-Somalia border - CGIAR Research Program on Policies, Institutions, and Markets (2020)
PIM researchers developed a toolkit to facilitate and strengthen a Multistakeholder Dialogue Platform to guide design and implementation of the Intergovernmental Authority for Development of the Horn of Africa’s cross border Biodiversity Management Programme in Kenya-Somalia, delivering biodiversity and livelihood benefits to local communities and benefitting roughly 3,000 farmers.